Religion and Politics Among the Jewish Leadership of Early Medieval Palestine - Tal Laufer (Religions)
This article investigates how the Jewish leadership in early medieval Palestine employed religious elements to consolidate its power among Jewish communities across the Muslim world. It suggests that the Palestinian Academy in Jerusalem leveraged its location to enhance its authority. The first section analyzes the 921/922 calendar dispute between the Palestinian and Babylonian Jewish centers. I argue that this ostensibly religious conflict was fundamentally a political struggle for leadership, demonstrating how religious authority was utilized for political gain. The second section examines the Hoshana Rabbah ceremony on the Mount of Olives, a key event presided over by the Palestinian Academy and its head, the Gaon. Taking place on the final day of Sukkot, this ceremony attracted Jewish pilgrims from across the Muslim world to Jerusalem. This part analyzes how the Palestinian Academy strategically employed this significant religious gathering—acknowledged even by rival Jewish centers—as a political demonstration to assert its leadership over the Jewish world. Furthermore, the analysis delves into the ceremony’s historical origins, the motivations behind its establishment, and its deep connection to Jerusalem.